Alpha, Beta, Delta, Omicron, and SARS-CoV-2 Breakthrough Cases: Defining Immunological Mechanisms for Vaccine Waning and Vaccine-Variant Mismatch - Hewins, Benjamin; Rahman, Motiur; Bermejo-Martin, Jesus F.; Kelvin, Alyson A.; Richardson, Christopher D.; Rubino, Salvatore; Kumar, Anuj; Ndishimye, Pacifique; Toloue Ostadgavahi, Ali; Mahmud-Al-Rafat, Abdullah; Kelvin, David J. (Frontiers in Virology, 2022)
The COVID-19 pandemic, caused by the SARS-CoV-2 coronavirus, is responsible for over 400 million cases and over 5.5 million deaths worldwide. In response to widespread SARS-CoV-2 infection, immunization of the global population has approached 60% one dose and 54% full dose vaccination status. Emerging data indicates decreasing circulating antibody levels as well as decreases in other immune correlates in vaccinated individuals. Complicating the determination of vaccine effectiveness is the concomitant emergence of novel SARS-CoV-2 variants with substantial antigenic differences from the ancestral D614G strain. The Omicron variant (B.1.1.529) spike protein has over 30 mutations compared with the D614G spike protein, which was used to design most SARS-CoV-2 vaccines in use today. Therefore, breakthrough cases of SARS-CoV-2 infections or severe disease in fully vaccinated individuals must be interpreted with caution taking into consideration vaccine waning and the degree of vaccine variant-mismatch resulting in adaptive immune evasion by novel emerging SARS-CoV-2 variants.